2013
DOI: 10.1136/practneurol-2013-000606
|View full text |Cite
|
Sign up to set email alerts
|

Hemiplegic shoulder pain: a common clinical consequence of stroke

Abstract: Hemiplegic shoulder pain is common in stroke survivors, developing in up to 54% of patients. The underlying mechanisms include soft tissue lesions, impaired motor function and central nervous system-related phenomena. Hemiplegic shoulder pain has many underlying causes and is challenging to manage, requiring a team approach, including physicians, therapists and caregivers. The management strategy must target the underlying causes. Preventative measures, such as positioning and handling, can reduce the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…The incidence of shoulder pain following stroke reported here is similar that reported by previous prospective studies 1,5 . Unfortunately, shoulder pain is not characterized by a specific definition and the quality of care of these hemiplegic patients widely varies by context and population 3 . It should be noted that our study population was younger than that of previous studies 1,5,9,10,11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of shoulder pain following stroke reported here is similar that reported by previous prospective studies 1,5 . Unfortunately, shoulder pain is not characterized by a specific definition and the quality of care of these hemiplegic patients widely varies by context and population 3 . It should be noted that our study population was younger than that of previous studies 1,5,9,10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…During the spastic recovery stage, spasticity patterns (adduction and internal rotation) may trigger pain 12 . In addition, subluxation and the need for transfer assistance, which may result in inappropriate pulley use, are important factors in shoulder pain after stroke 2,3,4 . Beside this, shoulder pain after stroke has been associated with a slower improvement in movement after stroke…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A larger number of participants in the current study also reported having pain when compared to a stroke sample in the United Kingdom. Although pain has not been identified as a symptom impacting on quality of life, shoulder pain is a common occurrence in patients with stroke which impacts on the functional ability of these individuals (Benlidayi & Basaran 2013). …”
Section: Discussionmentioning
confidence: 99%